Application of 2OMethylRNA antisense oligomer to control Candida albicans EFG1 virulence determinant - Araújo, Daniela (2019)
Antisense oligomers and their analogues have been successfully utilized to silence gene expression for the treatment of many human diseases; however the control of yeast´s virulence determinants has never been exploited before. In this sense, this work is based on the key hypothesis that if a pathogens genetic sequence is a determinant of virulence, it will be possible to synthesize a nucleic acid mimic based on antisense therapy (AST) that will bind to the mRNA produced, blocking its translation into protein and consequently reducing the pathogen virulent phenotype. EFG1 is an important determinant of virulence that is involved in regulation of Candida albicans switch from yeast to filamentous form. Thus, our main goal was to design and synthesize an antisense oligonucleotide (ASO) targeting the EFG1 mRNA and to validate its in vitro applicability. The results show that the anti-EFG1 2-OMethylRNA (2OMe) oligomer was able to significantly reduce the levels of EFG1 gene expression and of Efg1p protein translation (both approximately 60%), as well as effectively prevent filamentation of C. albicans cells (by 80%). Moreover, it was verified that anti-EFG1 2OMe keep the efficacy in different simulated human body fluids. Undeniably, this work provides potentially valuable information for future research into the management of Candida infections, regarding the development of a credible and alternative method to control C. albicans infections, based on antisense therapy methodology.